2016
DOI: 10.1016/j.watres.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater sludge dewaterability enhancement using hydroxyl aluminum conditioning: Role of aluminum speciation

Abstract: a b s t r a c tChemical conditioning is one of the most important processes for improve the performance of sludge dewatering device. Aluminum salt coagulant has been widely used in wastewater and sludge treatment. It is generally accepted that pre-formed speciation of aluminum salt coagulants (ASC) has an important influence on coagulation/flocculation performance. In this study, the interaction mechanisms between sludge particles and aluminum salt coagulants with different speciation of hydroxy aluminum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(27 citation statements)
references
References 32 publications
(41 reference statements)
1
22
1
1
Order By: Relevance
“…Meanwhile, the iron coagulants achieved better sludge dewaterability than the aluminium coagulants. Compared with previous studies, our study further confirmed this result using the high pressure filtration system.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Meanwhile, the iron coagulants achieved better sludge dewaterability than the aluminium coagulants. Compared with previous studies, our study further confirmed this result using the high pressure filtration system.…”
Section: Resultssupporting
confidence: 88%
“…Compared with the previous studies, sludge dewaterability was significantly related to EPS composition (i.e. TTAC, TTPN, and PS), and functional groups (i.e.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The market price of TiCl 4 was 8000 yuan per ton, while that of the commonly used inorganic salts -polymeric aluminum chloride (PACl) was around 2000 yuan per ton. According to our study, the optimal dosages of TSCs and PACl were 0.003 gTi/gTSS and 0.05gAl/gTSS for sludge conditioning respectively (Cao et al, 2016). The dosage of PACl is nearly ten times as much as that of titanium salt to achieve the same dewatering efficiency.…”
Section: The Economic Evaluation Of Tscs On Sludge Dewateringmentioning
confidence: 81%